2017
DOI: 10.1186/s41241-017-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and preventive therapies of radiation-induced xerostomia in head and neck cancer patient: a literature review

Abstract: Xerostomia or dry mouth is one of the most common and disturbing adverse effects following radiotherapy for head and neck cancer (HNC). This complication strongly increases the risk for dental caries, difficulties with chewing, swallowing and sleep disorders with significant impact on patients' quality of life. Current treatment approaches of xerostomia are often difficult and bring in many cases no substantial relief for the patient. This paper discusses the clinical features and current knowledge of xerostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
0
17
0
7
Order By: Relevance
“…One study showed that 97.5% of individuals complained of xerostomia at the end of radiotherapy [24]. The xerostomia is one of the most common and unpleasant side effects of radiotherapy of head and neck cancers [25].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that 97.5% of individuals complained of xerostomia at the end of radiotherapy [24]. The xerostomia is one of the most common and unpleasant side effects of radiotherapy of head and neck cancers [25].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of salivary biomarkers was limited by difficulties with collecting sufficient saliva for analysis as many participants had dry mouth or reduced saliva production, which can be a particularly common side effect of radiation for head and neck cancers 43 or a result of stress. 6 These challenges with salivary flow rate could complicate the interpretation of the data as decreased salivary flow can change concentrations of biomarkers in saliva, 6 while salivary biomarkers already suffer from debates around their reliability as they appear to respond at different time frames and intensities than the blood serum levels of the same biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Para a radioterapia comumente são utilizados aparelhos convencionais que possuem como principal desvantagem a aplicação de uma dose de radiação de modo impreciso e não localizado, afetando de maior grau os tecidos saudáveis que circundam o tumor (JAGUAR et al, 2010;LACERDA, 2014). Já a IMRT é uma técnica que permite a entrega da dose terapêutica com maior precisão ao tecido alvo, além de distribuir a dose heterogeneamente, sendo essa mais alta no tecido alvo, poupando desta maneira as glândulas salivares (JAGUAR et al, 2010;GIAFFERIS et al, 2017). Porém a técnica, além de cara, é muitas vezes inacessível na rede pública e possui algumas limitações (BRA-SIL, 2016).…”
Section: Diminuição Dos Danos Através Do Uso De Radioterapia De Intensidade Modulada (Imrt)unclassified
“…Uma das consequências indesejadas mais comum desse tratamento é a xerostomia, resultante dos danos às glândulas salivares provocados pela radiação que se manifestam através de um quadro de hiposecreção salivar que pode provocar diversas alterações bucais e dentárias patológicas (JAGUAR et al, 2010).…”
Section: Introductionunclassified